2016
DOI: 10.1007/s11340-015-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Material-Testing Machine for Study of Friction: Experimental Analysis of Machine Dynamics and Friction of Rock

Abstract: Experimental investigation of the coefficient of sliding friction in rock at normal stress and sliding velocity of typical earthquakes (10-100 MPa and 0.01-1 m/s) is necessary to develop velocity-dependent constitutive relations useful for earthquake rupture simulations. The velocity dependence of rock friction is best explored in parametric studies of interfacial friction by imposing step-like changes in velocity and measuring the frictional force, but such experiments are technically challenging. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…We suggest that with knowledge of surface temperatures and of the LT and RT of mm-scale contacts, which effectively provide critical constraints on the thermal state of the surface, determinations of temperature and contact properties will be more robust. Our calculations of normal stress distribution in the last few millimeters of HV sliding show greater stress concentration on mm-scale contacts than inferred by Saber (2017), primarily because of his uncertainty in the LT of contacts for conventional flat-ground surfaces. Nonetheless, Saber (2017) showed that hysteretic friction behavior during acceleration and deceleration could be better matched by using the observed surface-temperature distribution in coupled thermomechanical models of flash-weakening.…”
Section: Significance For Flash-weakening Modelmentioning
confidence: 59%
See 2 more Smart Citations
“…We suggest that with knowledge of surface temperatures and of the LT and RT of mm-scale contacts, which effectively provide critical constraints on the thermal state of the surface, determinations of temperature and contact properties will be more robust. Our calculations of normal stress distribution in the last few millimeters of HV sliding show greater stress concentration on mm-scale contacts than inferred by Saber (2017), primarily because of his uncertainty in the LT of contacts for conventional flat-ground surfaces. Nonetheless, Saber (2017) showed that hysteretic friction behavior during acceleration and deceleration could be better matched by using the observed surface-temperature distribution in coupled thermomechanical models of flash-weakening.…”
Section: Significance For Flash-weakening Modelmentioning
confidence: 59%
“…Our calculations of normal stress distribution in the last few millimeters of HV sliding show greater stress concentration on mm-scale contacts than inferred by Saber (2017), primarily because of his uncertainty in the LT of contacts for conventional flat-ground surfaces. Nonetheless, Saber (2017) showed that hysteretic friction behavior during acceleration and deceleration could be better matched by using the observed surface-temperature distribution in coupled thermomechanical models of flash-weakening. Experiments employing different velocity histories, different mm-scale contact LT and RT, and thermal imaging show great promise in enhancing our ability to perform more complete tests of the flash-weakening model for rock-on-rock friction.…”
Section: Significance For Flash-weakening Modelmentioning
confidence: 59%
See 1 more Smart Citation
“…strain gages, string potentiometers, and accelerometers) that provide information at a number of discrete points. [1][2][3][4]. However, the complex dynamic response of these sizable blades cannot be quickly or easily measured using a limited set of mounted accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is the development of a direct-shear testing machine that can impose a high velocity slip pulse, allowing for dm displacements, where the geometrical effects (slip-and velocity gradients) that affect traditional rotary shear experiments, are eliminated. Saber et al (2016) developed such a machine, allowing for displacements up to 4 cm. In addition, finding a way to probe temperature and pore fluid pressure locally within the actively slipping zone would significantly improve our capability of constraining the mechanisms responsible for dynamic weakening at (sub) seismic slip velocities, which is necessary in order to accurately incorporate these effects in numerical modelling of fault reactivation and any dynamically generated seismic wave field.…”
Section: Advances In Experimental Methodology Ii: High Velocity Expermentioning
confidence: 99%